Zika virus induces inflammasome activation in the glial cell line U87-MG. - Tricarico, Paola Maura; Caracciolo, Ilaria; Crovella, Sergio; D'Agaro, Pierlanfranco (Biochem Biophys Res Commun, 2017)
In the last years, neurological complications related to Zika virus (ZIKV) infection have emerged as an important threat to public health worldwide. ZIKV infection has been associated to neurological disorders such as congenital microcephaly in newborns and Guillain-Barré syndrome, myelopathy and encephalitis in adults. ZIKV is characterized by neurotropism and neurovirulence. Several studies have identified microglial nodules, gliosis, neuronal and glial cells degeneration and necrosis in the brain of ZIKV infected infants, suggesting that ZIKV could play a role in these neurological disorders through neuroinflammation and microglial activation. Little information is available about neuroinflammation and ZIKV-related neurological disorders. Therefore, we investigated if ZIKV is able to infect a glial cell line (U87-MG) and how the glial cell line responds to this infection in terms of inflammation (IL-1β, NLRP-3 and CASP-1), oxidative stress (SOD2 and HemeOX) and cell death. We observed a significant increase of ZIKV load in both cells and supernatants after 72 h, compared to 48 h of infection. We found that ZIKV infection induces an increase of IL-1β, NLRP-3 and CASP-1 genes expression. Significant increase of IL-1β and unchanged pro-IL-1β protein levels have also been detected. Moreover, we observed SOD2 and HemeOX increased gene expression mainly after 72 h post ZIKV infection. Subsequently, we found a decrease of U87-MG cell viability, after both 48 h and 72 h of ZIKV infection. Our results show that U87-MG cells are susceptible to ZIKV infection. ZIKV is able to successfully replicate in infected cells causing oxidative stress, NLRP3 inflammasome activation and subsequent release of mature IL-1β; this process culminates in cell death. Thus, considering the central role of neuroinflammation in neurological disorders, it is important to comprehend every aspect of this mechanism in order to better understand the pathogenesis of ZIKV infection and to identify possible strategies to fight the virus by rescuing cell death.
Keywords: Apoptosis; Cell Line; Cytokines; Humans; Immunity, Innate; Inflammasomes; Inflammation Mediators; Neuroglia; Oxidative Stress; Virus Replication; Zika Virus